A retrospective analysis of the clinical effects of neoadjuvant combination therapy with full-dose gemcitabine and radiation therapy in patients with biliary tract cancer. Issue 4 (April 2017) - Kobayashi, S.; Tomokuni, A.; Gotoh, K.; Takahashi, H.; Akita, H.; Marubashi, S.; Yamada, T.; Teshima, T.; Fukui, K.; Fujiwara, Y.; Sakon, M.
Abstract: Purpose: This study aims to evaluate survival and the objective response to neoadjuvant combination therapy with gemcitabine and radiation therapy in patients with biliary tract cancer. Methods: The chemoradiation therapy regimen consisted of 3 cycles of full-dose gemcitabine (1000 mg/m 2 at days 1, 8, and 15, every 4 weeks) with 50–60 Gy radiation. We compared 27 patients who received neoadjuvant chemoradiation therapy and 79 patients who were treated without neoadjuvant therapy. Hemi-hepatectomy or pancreatoduodenectomy was planned for all of the patients in the study population. CT-based staging was used to adjust for the pre-treatment characteristics of the patients. Results: After confirming the reproducibility of CT-based staging, we analyzed the survival of the patients. The multivariate analysis showed that the absence of arterial invasion on CT, the absence of lymph node swelling, and neoadjuvant therapy were independent prognostic factors. The three-year recurrence-free survival (RFS) rates in patients treated with and without neoadjuvant therapy were 78% and 58%, respectively ( P  = 0.0263). The adjusted overall survival (OS) (determined by the inverse probability of treatment weighting method using the inverse propensity score) was improved by neoadjuvant therapy ( P  = 0.00187); the hazard ratio was 0.3505. Conclusions: Neoadjuvant chemoradiation therapy might have the potential to improve RFS and OS. Registration: UMIN-CTR UMIN000015450